COMMUNICATION AND COMMUNION: A PSYCHOLOGICAL AND THEOLOGICAL APPROACH OF RELIGIOUS SUBJECT IN A DIGITAL WORLD - NECULA, Constantin; DUMULESCU, Daniela (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
The digital land brings a new subject to debate about the most appropriate framework to guide religion expression in online settings to promote the Church tradition mission and to build a spiritual identity in a world of crisis. In the last months, there were many voices stating that the Orthodox Church in Romania has a Communication problem. In order to understand the process of communication of the Church in a digital era, we need to underlie this process in the psychology and sociology of communication theories. Therefore, our analysis is an attempt to better understand the challenges derived from the communication of religious subject in a context saturated by media influence over social iconology of the Church and over spiritual communion and identity. We discuss different perspectives on framing information, on the relation between the Church mission as public communicator and media agenda. Finally, we identify some positive aspects of re-thinking communication process in order to increase the Church capacity of building a powerful strategy for social messages and educating communities in the culture of Truth. Moreover, the success of moral communication means opening a dynamic pastoral program incorporating psycho-sociological aspects of communication.